Mobile genetic element-encoded putative DNA primases composed of A-family polymerase—SSB pairs - Rice, Phoebe A. (Frontiers in Molecular Biosciences, 2023)
Mobile genetic elements can encode a wide variety of genes that support their own stability and mobility as well as genes that provide accessory functions to their hosts. Such genes can be adopted from host chromosomes and can be exchanged with other mobile elements. Due to their accessory nature, the evolutionary trajectories of these genes can differ from those of essential host genes. The mobilome therefore provides a rich source of genetic innovation. We previously described a new type of primase encoded by S. aureus SCCmec elements that is composed of an A-family polymerase catalytic domain in complex with a small second protein that confers single-stranded DNA binding. Here we use new structure prediction methods in conjunction with sequence database searches to show that related primases are widespread among putative mobile genetic elements in the Bacillota. Structure predictions show that the second protein adopts an OB fold (common among single-stranded DNA binding (SSB) proteins) and these predictions were far more powerful than simple sequence comparisons in identifying its homologs. The protein-protein interaction surface varies among these polymerase—SSB complexes appear to have arisen repeatedly by exploiting partial truncations of the polymerase’s N-terminal accessory domains.